Analisis Sistem Penjualan Kredit Pada Perum Perumnas Project Sukaramai Sentraland Medan - Chalista, Vidya; Lubis, Arnida (Balance : Jurnal Akuntansi dan Manajemen, 2022)
The purpose of this study was to analyze the credit sales system at Perum Perumnas Sentraland Medan and to find out how the performance of Perum Perumnas Sentraland Medan in implementing the credit sales system. In this study, data were collected using direct survey techniques to the field or on the object of research using interviews and documentation. The results of this study are 1. Perum Perumnas Sentraland Medan Project Sukaramai is one of the state-owned enterprises engaged in the development of public housing. 2. Perum Perumnas in its credit sales system involves the bank as a third party in the process of selling KPA-Bank credit. 3. Overall, the implementation of the credit sales system at Perum Perumnas Sentraland Medan is quite good